Scientific Paper Entitled: The Extent OF Healthcare Professionals' Awareness OF Service Quality And Patient Safety In The Government Healthcare Sector In The Kingdom Of Saudi Arabia (Journal of Namibian Studies : History Politics Culture, 2022)
The study aimed to assess healthcare professionals' awareness of service quality and patient safety in the government healthcare sector in the Kingdom of Saudi Arabia. The study utilized a descriptive-analytical approach to achieve its objectives. The study sample consisted of 200 healthcare professionals working in the government healthcare sector in Saudi Arabia. A questionnaire was used as the data collection instrument, and based on the results, the study reached several conclusions. Most notably, the participants strongly agreed on the axis of healthcare professionals' awareness of service quality and patient safety in Saudi Arabia, with an average score of 4.38. Their agreement ranged between 4.51 and 4.21, falling within the fifth category of the five-point scale, indicating strong agreement with the study's tool. This demonstrates consistency in the participants' agreement regarding healthcare professionals' awareness of service quality and patient safety in Saudi Arabia. The study also identified key suggestions to improve service quality and patient safety among healthcare professionals in Saudi Arabia. These include emphasizing cleanliness and sterilization in healthcare institutions, promoting personal hygiene among healthcare professionals, providing instant customer service and inquiries to meet patients' needs easily and quickly, maintaining patient records and confidentiality, ensuring credibility and honesty in dealings with patients, and building trust with patients. There were statistically significant differences at a significance level of 0.05 regarding healthcare professionals' awareness of service quality and patient safety in Saudi Arabia among healthcare professionals in the government healthcare sector, attributed to variables such as education, years of service, and training courses. Based on the results, the study recommends that healthcare authorities provide regular training courses for healthcare professionals to enhance their knowledge of service quality and patient safety. There should be a focus on educating healthcare professionals on the latest practices and international standards in healthcare safety and quality. The Ministry of Health should develop effective systems for monitoring service quality and patient safety and ensure their implementation across healthcare institutions.